(untitled) (Research, Society and Development, 2021)
Given the situations that the financial market can go through, mergers and acquisitions have major impacts on market efficiency, as discussed in classical finance theory. Therefore, the following work is based on the Efficient Markets Hypothesis for the application of the Event Study method for the analysis of Mergers and Acquisitions (M&A) of the regulated sectors of Electric Energy and Telecommunications in Brazil, to verify whether the decisions to allow mergers by the Administrative Council for Economic Defense (CADE) were assertive and if they had no anticompetitive impact on the market. For each sector, a variation of the Event Study method was used for the time windows analyzed, but its methodology was maintained. For the electricity sector, the mergers of Enel x CELG, 2017, and Enel x Eletropaulo, 2018, were contemplated, and for the Telecommunications sector the Telefónica x GVT acquisition of 2018 was analyzed. With the application of the method there is no evidence of interference in the competitive market, from the point of view of the capital market, for all the events contemplated, thus showing that the decisions of CADE proved correct and the market behaved efficiently.